The Effect of Service Recovery aAccessibility on Customer Satisfaction and Loyalty - Putri Syallom Paays (ITScience (Information Technology and Science), 2024)
Customer loyalty is a crucial aspect, especially in a business context because it has a big influence on the success and survival of a company. Therefore, loyal customers have an important role in the company's continued growth and greatly influence how much profitability the company will obtain. This research aims to analyze the influence of service recovery and accessibility factors on customer satisfaction and loyalty so that later it can contribute to increasing a deeper understanding of the factors that influence customer loyalty in the logistics sector. The population of this research is customers of the JNE expedition delivery service, the exact number of which is not known. The respondents for this research were 150 respondents with the criteria of JNE expedition service customers domiciled in Bekasi City with an age range of 18-60 years who had used expedition services at least twice in the last 3 months and had experienced problems using JNE expedition services. Data analysis using Structural Equation Modeling Partial Least Square. The research results show that Interactive Fairness and Outcome Fairness do not have a positive effect on customer satisfaction, but Procedural Fairness and Accessibility have a positive effect on customer satisfaction. Furthermore, Interactive Fairness does not have a positive effect on Customer Loyalty. However, Outcome Fairness, Procedural Fairness, Accessibility and Customer Satisfaction have a positive effect on Customer Loyalty.